The Possible Protective Effect of Taurine on Bisphenol Induced Structural Changes on the Cerebral Cortex of Rats: Histological and Immunohistochemical Study - Kandeel, Samah; Abd-Elsalam, Marwa M.; Abd-Elsalam, Sherief; Elkaliny, Heba H. (CNS & Neurological Disorders - Drug Targets, 2024)
Introduction: Bisphenol A (BPA) is a chemical compound that has been used in many industries, such as paints and dental sealants. Taurine is a semi-essential amino acid with antioxidant, anti-inflammatory, and anti-apoptotic actions. Aim: This study aimed to evaluate the possible protective effect of taurine on BPA-induced structural changes in the cerebral cortex of rats using histological and immunohistochemical methods. Methods: 35 Wistar rats (180-200 gm) were divided into control: 10 rats; Group I: 5 rats received corn oil (0.5 mL/day); Group II (Bisphenol low dose; BPAL): 5 rats received a low dose of BPA (25 mg/kg/three times/week); Group III (Bisphenol high dose; BPAH): 5 rats received a high dose of BPA (100 mg/kg/three times/week; Group IV: (BPAL + taurine): 5 rats received taurine 100 mg/kg/day and BPAL (25 mg/kg/three times/week); Group V: (BPAH + taurine): 5 rats received taurine 100 mg/kg/day and BPH (100 mg/kg/ three times/week). Results: BPAL& BPAH groups showed significant dose-dependent histological changes of the neuropil, pyramidal, and neuroglial cells at H stained sections, significantly increased GFAP, caspase- 3 immunohistochemical reaction with cells positive for Ki67 with many mitotic figures. BPAL + taurine and BPAH + taurine groups showed amelioration of the previously mentioned results. Conclusion: Taurine ameliorated the structural changes induced by BPA in the cerebral cortex of rats.
Keywords: bisphenol A